Investigating the Role of Social Capital in Recreating the Historical-Cultural Context of Shiraz - Marziyeh Medhat, Mohammad Taghipour (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study aimed to investigate the role of social capital in recreating the historical and cultural context of Shiraz. The predominant methodological approach of this research is quantitative, the information of which has been collected in the form of documents and surveys. To benefit from the views of the residents of the historical context of Shiraz and evaluate their views on the situation of social capital and its role in recreating the historical and cultural context of Shiraz, a questionnaire with closed questions has been used, which the sample size is 380 people at 95% confidence level and considering 10% error using the Cochran's formula. To analyze the data obtained from the questionnaires, examine the relationships between variables and test the research hypotheses, the descriptive and inferential statistical analyses, especially the sample t-test and Pearson correlation test in SPSS computer software environment were used. Based on the field findings, the components of social capital including networks of social participation, social trust, social cohesion and solidarity and social belonging in the historical-cultural context of Shiraz are at a low level. As a result of these conditions, the realization of regeneration programs in these neighborhoods will depend on strengthening the components of social capital among the residents of the historical-cultural context of Shiraz.